Recovery from rocuronium-induced neuromuscular block was longer in the larynx than in the pelvic limb of anesthetized dogs. (March 2017) - Sakai, Daniel M.; Martin-Flores, Manuel; Romano, Marta; Tseng, Chia T.; Campoy, Luis; Gleed, Robin D.; Cheetham, Jonathan
Abstract: Objective: To determine if neuromuscular monitoring at the pelvic limb accurately reflects neuromuscular function in the larynx after administration of rocuronium in anesthetized dogs. Study design: Prospective experimental study. Animals: Six healthy Beagle dogs. Methods: Anesthesia was maintained in dogs with isoflurane and a continuous infusion of dexmedetomidine. Rocuronium (0.6 mg kg −1 ) was administered intravenously to induce neuromuscular block. Train-of-four (TOF) impulses were applied to the left recurrent laryngeal nerve (RLn) and the peroneal nerve (Pn). The evoked TOF ratio (TOFR; T4:T1) was measured with electromyography (EMG) simultaneously at the larynx and at the pelvic limb. Spontaneous recoveries of T1 to 25% (T125% ) and 75% (T175% ) of twitch height, and to TOFR of 0.70 and 0.90 (TOFR0.90 ) at each EMG site were compared. Results: Data from five dogs were analyzed. Times to T125% were similar at the pelvic limb and larynx when measured by EMG; time to T175% was slower at the larynx by 6 ± 4 minutes ( p = 0.012). The larynx had a slower recovery to TOFR0.70 (41 ± 13 minutes) and TOFR0.90 (45 ± 13 minutes) than did the pelvic limb [29 ± 8 minutes ( p = 0.011) and 33 ± 9 minutes ( p = 0.003), respectively]. When the pelvic limb EMG returned to TOFR0.70 and TOFR0.90, the larynx EMG TOFR0.70 and TOFR0.90 values were 0.32 ± 0.12 ( p = 0.001) and 0.38 ± 0.13 ( p = 0.001), respectively. Conclusions and clinical relevance: After administration of rocuronium, neuromuscular function assessed by EMG recovered approximately 36% slower at the larynx than at the pelvic limb. The results in these dogs suggest that quantitative neuromuscular monitoring instrumented at a pelvic limb may be unable to exclude residual block at the larynx in anesthetized dogs.